Structural and Process Quality in Early Childhood Education and Care Provisions in Poland and the Netherlands: A Cross-National Study Using Cluster Analysis. Issue 4 (18th May 2020) - Wysłowska, Olga; Slot, Pauline L.
ABSTRACT: This cross-national study involved 56 toddler classrooms in Poland and the Netherlands. A cluster analysis was conducted to identify classroom profiles based on observed quality and these were compared regarding structural (group size and children-to-teacher ratio) and curriculum (e.g. pre-academics and pretend play) characteristics. In total, 224 video clips were evaluated with the CLASS Toddler and 130 teachers reported on structural and curriculum aspects. Research Findings : The findings for both countries showed moderate to high emotional support and low to moderate support for learning; the pattern of self-reported provision of activities was shaped alike. Three quality profiles were distinguished: i) high positive climate and support for learning, ii) overall low quality, iii) high emotional and low educational support. Overall, favorable structural conditions and a balanced curriculum including a broad range of activities were associated with highest process quality. Practice or Policy : A variety of different activities and high levels of developmentally stimulating interactions in an overall positive and warm classroom climate can support toddlers' broad development and learning. Professional development and a center's pedagogical policy and vision can play an important role in improving quality and implementing age-appropriate play and activities when an official curriculum is lacking.